2017
DOI: 10.1093/nar/gkx970
|View full text |Cite
|
Sign up to set email alerts
|

Common TFIIH recruitment mechanism in global genome and transcription-coupled repair subpathways

Abstract: Nucleotide excision repair is initiated by two different damage recognition subpathways, global genome repair (GGR) and transcription-coupled repair (TCR). In GGR, XPC detects DNA lesions and recruits TFIIH via interaction with the pleckstrin homology (PH) domain of TFIIH subunit p62. In TCR, an elongating form of RNA Polymerase II detects a lesion on the transcribed strand and recruits TFIIH by an unknown mechanism. Here, we found that the TCR initiation factor UVSSA forms a stable complex with the PH domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 54 publications
(72 reference statements)
1
72
0
Order By: Relevance
“…Importantly, we found that UVSSA contains a TFIIH-interacting region (TIR; amino acids 400-500), which is crucial for the association of TFIIH with stalled RNAPIIo. Consistently, it has been shown that the PH domain of p62 (1-108) associates with a small fragment in UVSSA (400-419) in vitro and that mutations within this region causes a defect in recovery of RNA synthesis in vivo 40 . Moreover, we found that the UVSSA ∆CIR mutant was not only unable to associate with CSA, but also with the TFIIH complex.…”
Section: Tfiih Recruitment To Dna Damage-stalled Rnapiio Is Dependentmentioning
confidence: 65%
See 3 more Smart Citations
“…Importantly, we found that UVSSA contains a TFIIH-interacting region (TIR; amino acids 400-500), which is crucial for the association of TFIIH with stalled RNAPIIo. Consistently, it has been shown that the PH domain of p62 (1-108) associates with a small fragment in UVSSA (400-419) in vitro and that mutations within this region causes a defect in recovery of RNA synthesis in vivo 40 . Moreover, we found that the UVSSA ∆CIR mutant was not only unable to associate with CSA, but also with the TFIIH complex.…”
Section: Tfiih Recruitment To Dna Damage-stalled Rnapiio Is Dependentmentioning
confidence: 65%
“…Biochemical in vitro experiments have shown that the association of CSB with RNAPII is sufficient to recruit TFIIH 23 . In addition, CSA was shown to associate with the p44 subunit of TFIIH 26 , while UVSSA can interact with the p62 subunit of TFIIH 40 . In agreement, we found that GFP-UVSSA associates with several subunits of the TFIIH complex in a UV-specific manner in vivo.…”
Section: Tfiih Recruitment To Dna Damage-stalled Rnapiio Is Dependentmentioning
confidence: 99%
See 2 more Smart Citations
“…Potentially, this could preclude XPB action during pol II transcription initiation at some genes. How does TFIIH function during DNA repair? The PH‐like domain of p62 has been shown to interact with several DNA repair factors in a process that is regulated in part by the chromatin remodeler CHD1 . How are these interactions controlled?…”
Section: Conclusion and Outstanding Questionsmentioning
confidence: 99%